2016
DOI: 10.1371/journal.pone.0161682
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Beta-Catenin Expression Is Disturbed in Systemic Lupus Erythematosus

Abstract: Wnt/β-catenin signaling is relatively understudied in immunity and autoimmunity. β-catenin blocks inflammatory mediators and favors tolerogenic dendritic cell (DC) phenotypes. We show here that leukocytes from lupus-prone mice and SLE patients express diminished β-catenin transcriptional activity, particularly in myeloid cells, although other leukocytes revealed similar trends. Serum levels of DKK-1, an inhibitor under transcriptional control of Wnt/β-catenin, were also decreased in lupus-prone mice. Surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Numerous studies have shown that the Wnt/β-catenin signaling pathway is involved in the occurrence and development of a variety of human cancers, such as colorectal, breast, prostate, and liver cancers (31)(32)(33)(34). Abnormalities in dendritic cells, B cells, CD4 + T cells, and other immune cells in the pathogenesis of SLE are also related to abnormal Wnt/β-catenin signaling (35)(36)(37). Furthermore, the JAK-STAT signaling pathway has been shown to play an important role in the occurrence and development of many types of hematological and solid tumors (38).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the Wnt/β-catenin signaling pathway is involved in the occurrence and development of a variety of human cancers, such as colorectal, breast, prostate, and liver cancers (31)(32)(33)(34). Abnormalities in dendritic cells, B cells, CD4 + T cells, and other immune cells in the pathogenesis of SLE are also related to abnormal Wnt/β-catenin signaling (35)(36)(37). Furthermore, the JAK-STAT signaling pathway has been shown to play an important role in the occurrence and development of many types of hematological and solid tumors (38).…”
Section: Discussionmentioning
confidence: 99%
“…Both human and LN MRL/lpr mouse studies indicated that the DKK-1 protein was significantly higher in the sera of SLE patients compared with control subjects, and the LN MRL/lpr mice exhibited a phenotype with an enhanced Wnt/ β -catenin activity, accompanied by an increased level of DKK-1 in the renal tissues and sera and an increased frequency of apoptotic cells of the renal tubular and renal interstitial tissues [ 30 ]. Notably, the beta-catenin transcriptional activity in leukocytes of lupus-prone mice and SLE patients was diminished, particularly in myeloid cells [ 31 ]. Such an activated Wnt signaling was further evidenced in human renal tissues of patients with LN by accessing β -catenin at both transcriptional and translational levels using assays including immunohistochemistry staining, qRT-PCR, and western blotting, suggesting that a dysregulated Wnt/ β -catenin signaling was related to the pathogenesis of LN and might play a role in the renal fibrosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level of β-catenin in PBMCs isolated from patients with acute uveitis was also reduced. Decreased β-catenin activity has previously been reported in leukocytes from lupus-prone mice and patients with systemic lupus erythematosus [ 37 ]. We also observed that decreased β-catenin activity inhibited the expression of Wnt-associated genes, such as Sox9 , Axin2 , Tcf1 , and Lef1 .…”
Section: Discussionmentioning
confidence: 99%